La fiebre del carbón - O'Dell, Tawni; Vázquez Nacarino, Eugenia; O'Dell, Tawni (Madrid : Siruela, 2013)
Coal mining community deputy Ivan Zoschenko remembers the injury that ended his football career, prepares for a former teammate's release from prison, and confronts a secret that has troubled his conscience.
Online resource; title from ePub title page (Digitalia, viewed April 15, 2016)
Keywords: Coal mines and mining -- Fiction; Ukrainian Americans -- Fiction; Football players -- Fiction; Male friendship -- Fiction; Family violence -- Fiction; Pennsylvania -- Fiction; Sheriffs -- Fiction; Wife abuse -- Fiction; Ex-convicts -- Fiction; Revenge -- Fiction; Psychological fiction; Electronic books